THE ALGORITHM OF BLOCK ENCRYPTION "AL03" AND THE RESULTS OF ITS ANALYSIS - Kapalova, Nursulu; Algazy, Kunbolat; Sakan, Kairat; Dyussenbayev, Dilmukhanbet (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2021)
This paper provides a brief description of the developed block cipher algorithm "AL03" and the results of checking the avalanche effect. This algorithm has the structure of a substitution-permutation network. The check consisted of two stages. At the first stage, the avalanche effect was tested separately for each transformation used in the algorithm. At the second stage, each round of encryption was analyzed. To characterize the degree of the avalanche effect in a transformation, the avalanche parameter is determined and used - the numerical value of the deviation of the probability of changing a bit in the output sequence when a bit in the input sequence changes from the required probability value equal to 0.5. The article presents the results after the 1st, 2nd, 3rd, and 24th rounds in the form of a table. Based on the round results obtained, comparative tests were carried out, as a result of which a positive conclusion was given on further research of this encryption algorithm.